NILAI MORAL DALAM SASTRA LISAN SENJANG MASYARAKAT SEKAYU MUSI BANYUASIN - Lestari, Dona; Nuzulia, Dian (Universitas PGRI Palembang, 2022)
Senjang is one of the oral literature that characterizes the Sekayu community, Musi Banyuasin. The purpose of this research was to determine the moral values contained in the oral literature of the Sekayu community, Musi Banyuasin Regency. Data in this study were collected through primary and secondary sources, primary sources obtained from research informants directly and secondary data through documentation and relevant research.